2014
DOI: 10.1186/gb-2014-15-1-r4
|View full text |Cite
|
Sign up to set email alerts
|

Global regulation of mRNA translation and stability in the early Drosophila embryo by the Smaug RNA-binding protein

Abstract: BackgroundSmaug is an RNA-binding protein that induces the degradation and represses the translation of mRNAs in the early Drosophila embryo. Smaug has two identified direct target mRNAs that it differentially regulates: nanos and Hsp83. Smaug represses the translation of nanos mRNA but has only a modest effect on its stability, whereas it destabilizes Hsp83 mRNA but has no detectable effect on Hsp83 translation. Smaug is required to destabilize more than one thousand mRNAs in the early embryo, but whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(151 citation statements)
references
References 81 publications
6
144
1
Order By: Relevance
“…Several other proteins acting as translational regulators have been reported in the fly embryo and oocyte [50][51][52][53][54][55][56][57], and in other eukaryotic species [58][59][60], oftentimes in a developmental context. These findings hint at the possibility that the regulatory principle implemented by bicoid protein and caudal mRNA in Drosophila may be at work also in other developmental systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other proteins acting as translational regulators have been reported in the fly embryo and oocyte [50][51][52][53][54][55][56][57], and in other eukaryotic species [58][59][60], oftentimes in a developmental context. These findings hint at the possibility that the regulatory principle implemented by bicoid protein and caudal mRNA in Drosophila may be at work also in other developmental systems.…”
Section: Discussionmentioning
confidence: 99%
“…Since these regulatory proteins bind to DNA, it is plausible that they could also bind to mRNA, thereby regulating translation; this is known to happen in the large class of homeodomain proteins [45][46][47] and for the Argonaute family proteins [48,49], for several other proteins that fulfill important functions in the Drosophila embryo and oocyte [50][51][52][53][54][55][56][57], but also in other eukaryotic species [58][59][60] and in prokaryotes [61][62][63][64][65][66][67]. Intuitively, each mRNA molecule could act as an independent sensor of the input concentration, and averaging over these multiple sensors could reduce the input noise and thereby allow for more effective information transmission at low input concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, Smaug inhibits translation by blocking the formation of a competent translation initiation complex (9,23), by promoting deadenylation of target mRNAs leading to their destabilization and degradation (24)(25)(26), and by micro-RNA-independent recruitment of Argonaute 1 (Ago1) to target mRNAs (27). RNA immunoprecipitation combined with microarray analysis demonstrated that Smaug binds directly to numerous embryonic fly RNAs, including those encoding glycolytic enzymes, and components of the proteasome regulatory particle, the TRiC/CCT chaperonin, and lipid droplets (28). In total, Smaug has been shown to destabilize ∼1,000 RNAs in fly embryos (2).…”
Section: Discussionmentioning
confidence: 99%
“…Early embryos provide a particularly attractive system for global studies of RNPs, as they are an established model for studies of post-transcriptional regulation, and there are a variety of genome-wide descriptions of mRNA behavior available that can facilitate analysis of such data. These include descriptions of mRNA stability, translation, and subcellular localization (De Renzis et al 2007;Lecuyer et al 2007;Qin et al 2007;Tadros et al 2007;Thomsen et al 2010;Dunn et al 2013;Chen et al 2014), which allow one to infer how RNP complexes function in post-transcriptional control based simply on the behavior of their component mRNAs (for examples, see Laver et al 2013Laver et al , 2015. Extrapolating from the results obtained from the highthroughput pipeline reported here, it should be feasible to produce antibodies against two-thirds of Drosophila RNP complex proteins or, indeed, of the RNP complex proteins from any organism, in a single high-throughput screen.…”
Section: Global Characterization Of Rnp Components and Functionsmentioning
confidence: 99%
“…Studies in recent years have sought to gain a genome-wide view of the activity of RNPs (Tenenbaum et al 2000(Tenenbaum et al , 2002Ule et al 2003Ule et al , 2005Gerber et al 2004;Keene 2007;Hogan et al 2008;Morris et al 2010;Laver et al 2013Laver et al , 2015Chen et al 2014;Stoiber et al 2015). One powerful approach involves the identification of all of the RNA and protein components of particular RNPs by immunoprecipitation (IP) of the protein of interest followed by identification of the associated transcripts by microarray or next-generation sequencing analysis, and identification of the associated proteins by mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%